2020
DOI: 10.1007/s11136-020-02427-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life following road traffic injury: the impact of age and gender

Abstract: Purpose The impact of road traffic crashes on health is well developed, in terms of deaths and direct consequences, but it is less so in terms of long-term life consequences. Few studies have compared the general impact on Health Related Quality of Life (HRQoL) following road traffic injury (RTI) by using a variety of different injured body parts and severity levels of the injury and compared them with a sample of non-injured referent individuals. Consequently, the aim of the current study is to assess how inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 24 publications
(36 reference statements)
2
16
0
Order By: Relevance
“…The Croatian general population sample reported lower QoL scores in the older age group and among females ( 24 ). Other studies of RTA victims also found older age to be associated with lower QoL after the RTA ( 4 , 5 , 6 , 9 , 11 , 23 , 25 , 26 , 27 ). A few studies also found female RTA survivors reporting lower QoL than males ( 5 , 25 , 28 ).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…The Croatian general population sample reported lower QoL scores in the older age group and among females ( 24 ). Other studies of RTA victims also found older age to be associated with lower QoL after the RTA ( 4 , 5 , 6 , 9 , 11 , 23 , 25 , 26 , 27 ). A few studies also found female RTA survivors reporting lower QoL than males ( 5 , 25 , 28 ).…”
Section: Discussionmentioning
confidence: 77%
“…Other studies of RTA victims also found older age to be associated with lower QoL after the RTA ( 4 , 5 , 6 , 9 , 11 , 23 , 25 , 26 , 27 ). A few studies also found female RTA survivors reporting lower QoL than males ( 5 , 25 , 28 ). Lower education level ( 7 , 11 , 12 ), unemployment ( 6 , 9 , 11 ) and lower economic status ( 11 ) of RTA victims were associated with lower QoL after the RTA in several studies.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…CVT project and relevant legislation [37]; [39,40]; [42][43][44][45][46][47] Infrastructure projects assessment [2][3][4][5][6][7]; [14]; [18] Social impacts of road traffic [3,4]; [11]; [17,18]; [49]; [50] Influence of the road system on the natural and urban landscape and the quality of the habitat [8,9]; [13]; [16,17]; [19]; [20]; [21,22] Influence of the road system on air quality [4]; [13]; [23][24][25][26][27] Influence of the road system and city morphology on noise pollution [4]; [12]; [23][24][25][26][27][28][29]…”
Section: Themes Referencesmentioning
confidence: 99%
“…Less research focused on long-term health-related quality of life (Rissanen et al, 2020;Gopinath et al, 2017); which remains very limited, almost non-existent in the context of MLA limitations and educational status. The proposed study assessed the effects of education on the major life activities of RTI victims concerning health satisfaction status.…”
Section: Introductionmentioning
confidence: 99%